Different Types of Gene Expression Profiles and Pathway Enrichment Analysis of Oral Dysplastic Keratinocyte Cells Caused by Heavy Smoking - Sengupta, Sudeshna; Bhattacharya, Malavika (Asian Journal of Biological and Life Sciences)
Aim/Background: The aim of the study is to carry out survival analysis on the candidate hub genes to check out their effects on Keratinisation of mucous cells are related to the genes which are responsible for OSCC. Materials and Methods: Gene expression profiling array for two microarray data sets of keratinized and normal oral tissue has been taken from GEO then DEGs and lnc RNAs are identified in oral cancer using LIMMA R package 15 in bio-conductor followed by KEGG analysis. STRING tool used to construct the PPIN for the sub PPIN, MCODE algorithm used for our work. The prognostic correlation co efficient values of the genes responsible for the keratinisation process in cancers have been studied using TCGA project in The Encyclopedia of RNA Interactomes (ENCORI). Functional annotation and co-expression results done with these CD44, CD58, CD40, VIM, KRT19, MMP1, ANGPTL4, FABP4, ENTPD1, and FCER2 key protein coding genes. Results: Hyper-methylated promoters play a crucial role in the inactivation suppressor genes during carcinogenesis and dysregulation of the DEGs are intently related with progression of cancer as functions as reporter genes. The enrichment result of DEGs can reveal the role of some URGs shows various activated levels in keratinocyte cells of heavy smokers and keratinocytes of people who had never smoked. ENTPD1 is connected to the DEGs which are related to TNF receptor, lymphocyte receptor. Ag3 associated with lymphocytes respectively, also to KRT19 which together acts with KRT8 causes mutations and alterations of genes. Conclusion: From this study a hallmark gene ENTPD1 has been identified for oral squamous cell carcinoma along with HNSCC with the seed gene CD44 interconnected with CD40, CD58.
Keywords: Differentially expressed genes; Hallmark gene.; Head and neck squamous cell carcinoma; Keratinisation; Oral squamous cell carcinoma